Trends of the development of rural schools in Ukraine (1972-1984 YEARS) - Hanna Ivaniuk (Vasyl Stefanyk Precarpathian National University, 2017)
The article presents the results of historical and educational research of rural schooldevelopment in Ukraine. Disclose the effect of social order for education students in ruralschools, regulatory support their activities. The study is based on the key idea external-schooldifferentiation of rural school development that was characteristic of the period,"Transformation of rural schools and finding ways to overcome the differences with the urbanschool." Within this period reveals the essence of tasks meaningful methodological andorganizational support of rural schools in the stage of "Unification of activity of rural school(1972-1984)." It is identified as positive trends, as well as those that hampered theprogressive development of the rural school. Key words: development trends, rural school, the content of education, the reform ofsecondary school, the purpose of education, training programs, curricula.